2003
DOI: 10.1046/j.1440-1754.2003.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary pulmonary hypoplasia: A case report and review of the literature

Abstract: A case of primary pulmonary hypoplasia in a term female neonate presenting with severe respiratory distress at birth is reported. Respiratory failure persisted and she died at 12 days of age. Primary pulmonary hypoplasia is a rare condition not associated with other maternal or fetal disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Respiratory distress in the first five minutes following birth is typical for these patients, and they usually require mechanical ventilation. Apgar scores are usually found to be lower, although babies with completely normal Apgar scores may also be seen [11,[15][16][17][18][19]. However, as in our patient, patients who remain asymptomatic until puberty have also been reported [7,9,10].…”
Section: Copyright © 2011 Sciresmentioning
confidence: 53%
See 1 more Smart Citation
“…Respiratory distress in the first five minutes following birth is typical for these patients, and they usually require mechanical ventilation. Apgar scores are usually found to be lower, although babies with completely normal Apgar scores may also be seen [11,[15][16][17][18][19]. However, as in our patient, patients who remain asymptomatic until puberty have also been reported [7,9,10].…”
Section: Copyright © 2011 Sciresmentioning
confidence: 53%
“…Pulmonary hypoplasia is characterized by reduced and/or less developed lung tissue to varying degrees [7][8][9][10]. When pathologic specimens of the patients with pulmonary hypoplasia were examined, it was found that ratio of lung weight/body weight of the patients was less than 0.012 [11]. Development of bronchial tree occurs in 26th to 31st days of intrauterine life.…”
Section: Discussionmentioning
confidence: 99%
“…It may be caused by an embryologic defect of the lung or vascular tissues, as in congenital acinar dysplasia [6,7] or by an in utero vascular accident. Only a few cases of primary unilateral pulmonary hypoplasia have been described in the literature with varying degrees of severity ranging from complete hypoplasia of one lung to simple hypoplasia of an isolated lobe [1,5,6,8,9], including in familial series [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Unilateral pulmonary hypoplasia or agenesis is a rare cause of respiratory distress in the neonate [1,8,9]. Most cases are secondary to conditions that limit fetal lung growth such as diaphragmatic hernia or bronchial stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…1), the result of abnormal antenatal lung growth, is common, being present in 15 to 20% of early neonatal deaths. It may be primary [1], but more usually occurs secondary to a variety of insults which can be largely divided into those which reduce intra-thoracic space, fetal breathing movements or amniotic fluid volume. It is also found in association with trisomy 18 and 21 [2].…”
Section: Introductionmentioning
confidence: 99%